Review of Effi Gazi, Άγνωστη χώρα: Ελλάδα και Δύση στις αρχές του 20ού αιώνα: [Unknown land: Greece and the West at the beginning of the 20th century] - Stamos, Yannis (Historein, 2025)
Review of Effi Gazi. Άγνωστη χώρα: Ελλάδα και Δύση στις αρχές του 20ού αιώνα [Unknown country: Greece and the West at the beginning of the 20th century]. Athens: Polis, 2020. 368 pp.